UJI AKTIVITAS ANTIOKSIDAN FRAKSI AIR DAUN KRATOM (MITRAGYNA SPECIOSA) - Hema Novita Rendati (Lembaga Pendidikan dan Penelitian Manggala Institute, 2026)
Kratom leaves (Mitragyna speciosa) are traditionally used as a natural remedy and are known to contain various secondary metabolites with antioxidant potential. This study aimed to activate the antioxidant activity of the aqueous fraction of kratom leaves in vitro. Kratom leaves were extracted using methanol, then liquid-liquid fractionation was performed to obtain the air fraction. Phytochemical screening was performed qualitatively, while antioxidant activity was evaluated using the DPPH, ABTS, and FRAP methods. The phytochemical screening results showed that the air fraction contained alkaloids, phenolic compounds, tannins, quinones, saponins, and steroids/terpenoids, but no flavonoids were detected. Antioxidant activity tests showed that the air fraction exhibited strong antioxidant activity in the DPPH and ABTS methods, with IC₅₀ values of 66.69 ppm and 79.99 ppm, respectively, while the FRAP method showed moderate activity with an IC₅₀ value of 210.88 ppm. The difference in activity between the methods indicates that the air fraction is more effective as a free radical scavenger than as a reducing agent. Based on these results, the air fraction of kratom leaves has potential as a natural antioxidant source. However, further research is needed to identify specific active compounds and to assess biological activity in vivo.